Hubungan antara Kekuatan Otot Lengan dan Fleksibilitas Pergelangan Tangan terhadap Ketepatan Servis Long Forehand di Ekstrakurikuler Bulutangkis SMA Negeri 1 Kota Sukabumi Tahun 2018 - Nurjamilah Barakat; Firman Maulana; Bachtiar Bachtiar (utile: Jurnal Kependidikan, 2018)
This study aims to determine the arm muscle strength, wrist flexibility, and know their contribution to the accuracy of long forehand service precision. The type of this research uses servey. The population of this research is 30 people, the sample is taken by total sampling. Arm muscle strength data obtained from push up, wrist flexibility data obtained from test goniometer, the long forehand service precision data obtained from long serve test. Data were analyzed by using correlation techniques and contribution (r2 x 100%) with significance level Î± 0,05. Data analisis of the arm muscle strength was obralned rscore = 0,543 and rtable = 0,374. Its contribution to the accuracy of long forehand service precision is 29,48%. Data analysis of wrist flexibility was obralned rscore = 0,559 and rtable = 0,374. Its contribution to the accuracy of wrist flexibility is 31,24%. Analysis of arm muscle strength data and wrist flexibility joint together contributed 44,35% to the accuracy of long forehand service precision.